Availability of Tracer Drugs and Implementation of Their Logistic Management Information System in Public Health Facilities of Dessie, North-East Ethiopia - Demessie MB; Workneh BD; Mohammed SA; Hailu AD (Dove Medical Press, 2020)
Mulate Belete Demessie,1 Birhanu Demeke Workneh,1 Solomon Ahmed Mohammed,1 Abel Demerew Hailu2 1Department of Pharmacy, College of Medicine and Health Science, Wollo University, Dessie, Ethiopia; 2Department of Pharmacy, Dessie Health Science College, Dessie, EthiopiaCorrespondence: Solomon Ahmed MohammedDepartment of Pharmacy, College of Medicine and Health Science, Wollo University, P.O. Box: 1145, Dessie, EthiopiaTel +251 91 050 4378Email ahmedsolomon21@gmail.comBackground: Tracer drugs are the representative of essential medicines and satisfy the priority healthcare needs of the population. Managing tracer drugs through logistics management information systems is a strategy to enhance their smooth flow for continuous provision of quality health service. This study assessed the availability of tracer drugs and implementation of their logistic management information system in public health facilities of Dessie, North-East Ethiopia.Methods: Cross-sectional study was conducted from September 15– 30, 2017, in all public health facilities of Dessie. The data were collected by reviewing tracer drugs logistic formats and conducting physical inventory. Key informant interview was employed to all pharmacy heads and store managers. Data analysis was done using statistical package for social science version 20 and Microsoft Excel 2010.Results: Twelve tracer drugs were managed by health facilities. The overall mean availability, mean duration, and average frequency of stock out of tracer drugs (last 6 months) were 74.7%, 48.8 days, and 1.43, respectively. In eight health facilities, logistic records were available, but all health facilities did not use stock cards. Also, 3 out of 9 used the health commodity management information system. On average, 77.8% of the tracer drugs had bin cards, of which, 86% were updated. The discrepancy between physical count and stock keeping records was ranged from 0% to 100%. The causes of stock out were inadequate supply, lack of recording forms, and their inconsistent use.Conclusion and Recommendations: The availability of tracer drugs was less than the recommended percent, and inadequate supply, poor availability and use of recording forms were the reasons for stock out. Thus, health facility managers and pharmacy heads should work in harmony to ensure uninterrupted supply and implement a logistic management information system.Keywords: logistic management information system, overstock, public health facility, stockouts, tracer drugs